2015
DOI: 10.1039/c4dt03691c
|View full text |Cite
|
Sign up to set email alerts
|

Architectural control of urea in supramolecular 1D strontium vanadium oxide chains

Abstract: A facile bottom-up approach for the controlled self-assembly of infinite strontium vanadium oxide chains is presented. Two novel one-dimensional strontium-linked polyoxovanadate chains have been isolated by linkage of decavanadate clusters with strontium(ii) ions. To control the architecture dimensions, urea was used as a critical control parameter which allowed tuning of the intra- and intermolecular spacings within the crystal lattice. Using N,N-dimethyl formamide (DMF) and urea as stabilizing ligands, a sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Here, we explore the possibility of linking individual {V 12 } units into supramolecular chains, similar to a classical organic polymerization. To avoid additional complexities arising from the use of redox-active linkage metal ions, we opted to use strontium-functionalized dodecavanadates, as in previous studies we had successfully linked decavanadate clusters using Sr 2+ cations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we explore the possibility of linking individual {V 12 } units into supramolecular chains, similar to a classical organic polymerization. To avoid additional complexities arising from the use of redox-active linkage metal ions, we opted to use strontium-functionalized dodecavanadates, as in previous studies we had successfully linked decavanadate clusters using Sr 2+ cations …”
Section: Resultsmentioning
confidence: 99%
“…Pioneering work highlighted the assembly of multidimensional framework materials formed by linking mixed-valent polyoxovanadates with 3d transition metals or alkaline earth metals . Furthermore, POMs were linked via Ag I -based bridging units which has led to several 1D chains and 2D grids. Later studies were focused on the linkage of POMs through transition metals or lanthanides, leading to a multitude of supramolecular aggregates. Based on these guiding design principles, we have recently started to explore the linkage of vanadium oxide clusters with large alkali or alkaline earth metals as potential models for industrial catalysts, e.g., those used in the oxidative dehydrogenation of alkanes. By the use of Sr II or Ba II cations, we gained access to a series of large supramolecular clusters and 1D strontium or barium vanadium oxide chains . In these studies, we noted that the bulkiness of the solvent ligands employed significantly affects the resulting supramolecular architectures. Further architectural control was achieved by using additional organic linkers such as urea …”
Section: Introductionmentioning
confidence: 99%
“…26,27 In recent years, many M-POV structures have been reported, many of these are yet untested as SSPs. For example, could [Sr(DMF)2.5(CON2H4)2]2[H2V10O28] (DMF=dimethylformamide) and (n-Bu4N)4[Cu6V30O82(NO3)2(CH3CN)6], 124,125 access MV2O6 (M = Sr, Cu) materials useful as sensors, photocatalysts and photoanodes? 126,127…”
Section: Mixed-metal Polyoxometallates (M-poms)mentioning
confidence: 99%
“…Several studies have been reported on the formation of 1D POM chains, comprised of barium vanadates (Kastner & Streb, 2013), tetrarubidium decavanadates (Yakubovich et al, 2015), strontium vanadium oxides (Schwarz & Streb, 2015) and octamolybdates (Rosnes et al, 2012), but the phenomenon behind their formation was not discussed. In this work, we demonstrate a simple one-pot synthetic method for growing 1D inorganic chains of K(C 6 H 16 N) 3 Mo 8 O 26 ÁH 2 O from its colloidal phase through the variation of pH.…”
Section: Introductionmentioning
confidence: 99%